The Influence of Current Ratio, Inventory Turnover Ratio, Cash Turnover and Debt to Equity Ratio Against the Return on Investment in The Production of Industrial Companies Listed on The Stock Exchange Of Malaysia In 2016 - Rika Umniati, Kartika Hendra Titisari & Yuli Chomsatu (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research aims to know the influence of Current Ratio, Inventory TurnoverRatio, Cash Turnover and Debt To Equity Ratio against the Return On Investment.The population in the study, namely the production of industrial companies listedon the stock exchange of Malaysia Year 2016 totalling 233 companies. Type of thisresearch is quantitative research. Sampling using a purposive sampling technique.The number of samples as many as 131 research company. Methods of dataanalysis used in the study are using multiple linear regression test. Data analysisusing SPSS 17 assistance. The results of this study indicate that a variableInventory Turnover Ratio effect on Return On Investment. While the Current Ratio,variable Cash Turnover and Debt To Equity Ratio has no effect against a ReturnOn Investment.Keywords: Current Ratio, Inventory Turnover Ratio, Cash Turnover, Debt To Equity Ratio,Return On Investment